2000
DOI: 10.2527/2000.784817x
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine studies in ivermectin-treated heifers from birth to puberty.

Abstract: Continuous treatment with ivermectin from birth to puberty advanced sexual maturation by 3.7 wk in Holstein heifers grazing pastures naturally infected with nematodes. Every 14 d jugular blood samples were taken from birth to 45 wk of age from all heifers. No differences in serum FSH, estradiol, or thyroxine levels were observed during the trial between the treated and untreated group. Mean LH levels were diminished in untreated heifers 4 wk before the first estrus and the amplitude of LH pulses was augmented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 44 publications
2
32
0
3
Order By: Relevance
“…Furthermore, parasites in cows during the periparturient period were related to impaired milk production (Perri et al, 2011). The effects of gastrointestinal parasites, both on development and production itself, were associated with altered profiles of circulating metabolic hormones (Lacau-Mengido et al, 2000Díaz-Torga et al, 2001;Perri et al, 2011). Maximal levels of IGF-1 reached during prepuberty were lower in untreated than in ivermectin treated heifers (Lacau-Mengido et al, 2000) and time of prepubertal increase in serum leptin levels was delayed in untreated heifers (Díaz-Torga et al, 2001).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, parasites in cows during the periparturient period were related to impaired milk production (Perri et al, 2011). The effects of gastrointestinal parasites, both on development and production itself, were associated with altered profiles of circulating metabolic hormones (Lacau-Mengido et al, 2000Díaz-Torga et al, 2001;Perri et al, 2011). Maximal levels of IGF-1 reached during prepuberty were lower in untreated than in ivermectin treated heifers (Lacau-Mengido et al, 2000) and time of prepubertal increase in serum leptin levels was delayed in untreated heifers (Díaz-Torga et al, 2001).…”
Section: Introductionmentioning
confidence: 97%
“…The IGF-1 RIA was performed after acid-ethanol extraction as described in Lacau-Mengido et al (2000). The IGF-1 antibody (UB2-495) of the NIDDK was used.…”
Section: Hormone Determinationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For IGF-I RIA serum samples (15 µl) and standards were subjected to the acid-ethanol cryoprecipitation method as previously described (Lacau-Mengido et al 2000). IGF-I was determined using an antibody (UB2-495) provided by Drs L Underwood and J J Van Wyk, and distributed by the Hormone Distribution Program of the NIDDK.…”
Section: Riasmentioning
confidence: 99%
“…The e n d o c r i n e m e c h a n i s m s c o n t r o l l i n g o v a r i a n development and sexual maturation are also becoming clear [14]. Endocrinological studies on several species have found that follicular growth correlates with serum concentrations of follicle stimulating hormone (FSH), which together with luteinizing hormone (LH), gradually increases from birth to puberty [9,11]. Recent studies in heifers and rats have shown that an increase in FSH and LH in neonatal calves activated follicular growth in the ovaries [6,11,14], that an increase in FSH induced new follicular growth in a wave-like manner in neonatal calves, and that the growing stage of follicles with the ability to secrete of estradiol gradually progressed until puberty [11,14].…”
mentioning
confidence: 99%